2012
DOI: 10.1021/es3029236
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Uncertainty Analysis of Life Cycle Assessment for Algal Biofuel Production

Abstract: As a result of algae's promise as a renewable energy feedstock, numerous studies have used Life Cycle Assessment (LCA) to quantify the environmental performance of algal biofuels, yet there is no consensus of results among them. Our work, motivated by the lack of comprehensive uncertainty analysis in previous studies, uses a Monte Carlo approach to estimate ranges of expected values of LCA metrics by incorporating parameter variability with empirically specified distribution functions. Results show that large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
177
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(189 citation statements)
references
References 54 publications
9
177
0
Order By: Relevance
“…The application of results to microalgae biorefinery systems is limited. Additionally, several techno-economic and life cycle assessments of the microalgae biofuel process do not consider the impact of storage time or preprocessing temperatures on yield as all assume a seamlessly integrated co-located growth and processing facility (Batan et al, 2010;Beal et al, 2012;Sills et al, 2012;Jones et al, 2014;Quinn et al, 2014;Rogers et al, 2014;Thilakaratne et al, 2014;Woertz et al, 2014). Current assessments of the microalgae to biofuels process make simplifying assumption due to the lack of large-scale processing data .…”
Section: Introductionmentioning
confidence: 99%
“…The application of results to microalgae biorefinery systems is limited. Additionally, several techno-economic and life cycle assessments of the microalgae biofuel process do not consider the impact of storage time or preprocessing temperatures on yield as all assume a seamlessly integrated co-located growth and processing facility (Batan et al, 2010;Beal et al, 2012;Sills et al, 2012;Jones et al, 2014;Quinn et al, 2014;Rogers et al, 2014;Thilakaratne et al, 2014;Woertz et al, 2014). Current assessments of the microalgae to biofuels process make simplifying assumption due to the lack of large-scale processing data .…”
Section: Introductionmentioning
confidence: 99%
“…Wet solvent extraction of lipid from microalgae biomass which eliminates the need for drying and potentially reducing energy input may be possible, but has yet to be proven at industrial scale (de Boer et al 2012;Lardon et al 2009;Sills et al 2012); but for microalgal biofuels to yield net gains in energy lipid extraction methods for wet biomass must be developed (Sills et al 2012;Delrue et al 2012). …”
Section: Biodiesel and Trans-esterificationmentioning
confidence: 99%
“…A reworking of the data from 6 LCAs, in what was termed a Meta-model of Algae Bio-Energy Life cycles (MABEL), found that the energy return on energy invested (EROI) ranged from one, no return on the energy invested to two, twice the energy invested . A recent extensive review and LCA using a Monte Carlo approach to estimate ranges of expected values found that nearly half of all the LCA results had an EROI of less than one (Sills et al 2012). The Sills (2012) study also showed that methane from anaerobic digestion of defatted microalgae is required for net gains in energy and must be an integral part of microalgal biodiesel production process to yield EROI values that are greater than one.…”
Section: Biodiesel and Trans-esterificationmentioning
confidence: 99%
“…Achieving an energy return based on the production of biodiesel alone is extremely challenging, however, with 50% of studies on microalgal biodiesel reporting an EORI of <1 [10][11][12][13]. Anaerobic digestion of wet microalgae is potentially an energetically more favourable option as it utilises the entire biomass and does not require drying before digestion [9,[14][15][16] One of the major challenges in achieving an energy return from the production of biofuel from microalgae is harvesting and concentrating the algae [3,17,18]; this is due to a number of factors including the dilute nature of the algal suspension at 0.02%-0.05% dry solids [19,20]; the small size of micro-algal cells (most algae are below 30 µm) [21]; the similarity in density of the algal cells to that of the growth medium [22]; and the negative surface charge on the algae that results in dispersed stable algal suspensions [23][24][25].…”
Section: Introductionmentioning
confidence: 99%